The Effect of Using E-Tickets On Tourist Satisfaction At The Istano Basa Pagaruyuang Tourist Attraction - Mandalia, Siska; Nabila Khairunnisa (Samarinda State Polytechnic, 2023)
Abstract This study aims to determine the effect of using e-tickets on tourist satisfaction at the Istano Basa Pagaruyuang tourist attraction West Sumatera. The variables used in this study are using e-tickets as the independent variable and the tourist satisfaction variable as the dependent variable. The research method uses a quantitative approach with a simple linear regression test to determine the direct influence between variables. The population in this study were all tourists who visited Istano Basa Pagaruyuang. The research sample totaled 100 respondents because it used a probability sampling technique with random sampling based on chance. The data collection technique was carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. The data were processed using the SPSS version 25 application program. The results showed that the use of e-tickets had a significant effect on tourist satisfaction. Keywords: Tourist Attractions, E-ticket, Tourist Satisfaction, Istano Basa Pagaruyuang